2014
DOI: 10.1111/syen.12089
|View full text |Cite
|
Sign up to set email alerts
|

An integrative approach to species discrimination in the Eupelmus urozonus complex (Hymenoptera, Eupelmidae), with the description of 11 new species from the Western Palaearctic

Abstract: The systematics of the European species of Eupelmus (Eupelmus) Dalman (Hymenoptera: Eupelmidae) belonging to the 'urozonus-complex' is elucidated through combined molecular and morphological characterization. One mitochondrial gene fragment (Cytochrome oxidase I) and one nuclear protein-coding gene fragment (Wingless) were sequenced and the results compared with those of a detailed morphological study of the specimens from an extensive sampling. Knowledge of the biodiversity of Eupelmus in the Western Palearct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 67 publications
(68 reference statements)
1
39
1
Order By: Relevance
“…From our point of view, this demonstrates that molecular markers cannot always be used alone to delimit species, but instead should be complemented with ecological and morphological data (Tan et al ., ). Genetically described cryptic species nevertheless provide a framework for more exhaustive morphological examination of the specimens to develop diagnostic characters (Baur et al ., ; Al Khatib et al ., ). Such an integrative taxonomic approach will be very powerful in disentangling the cryptic and functional diversity among Aphidiinae if combined with laboratory experiments, such as crossing between putative cryptic species or host acceptance, to confirm the host specialization suggested here (for aphid species that can be reared in the laboratory).…”
Section: Discussionmentioning
confidence: 97%
“…From our point of view, this demonstrates that molecular markers cannot always be used alone to delimit species, but instead should be complemented with ecological and morphological data (Tan et al ., ). Genetically described cryptic species nevertheless provide a framework for more exhaustive morphological examination of the specimens to develop diagnostic characters (Baur et al ., ; Al Khatib et al ., ). Such an integrative taxonomic approach will be very powerful in disentangling the cryptic and functional diversity among Aphidiinae if combined with laboratory experiments, such as crossing between putative cryptic species or host acceptance, to confirm the host specialization suggested here (for aphid species that can be reared in the laboratory).…”
Section: Discussionmentioning
confidence: 97%
“…Given the lack of dichotomous keys for separating T. flavipes , the possible existence of cryptic species in this taxa and the genus Eupelmus , as well as the recent revision of Palaearctic species by Al Khatib et al . (), analyses were performed based on aggregated data at the genus level for Eupelmus spp. and at the morphospecies level for T. flavipes .…”
Section: Methodsmentioning
confidence: 99%
“…11.10, 11.95 and 12.56 ∘ C for pupae, pharate adults and emerged adults, respectively). These values were used to calculate the degree-days with Eqn (1) a Molecular data demonstrated that this was a complex comprising at least two different species (Kaartinen, et al, 2010;Al Khatib et al, 2014). Ha, high altitude; La, low altitude.…”
Section: Phenology Model and Emergence From Gallsmentioning
confidence: 99%
“…Statements, such as “smaller specimens can be very difficult, if not impossible, to identify correctly because the morphology of typical specimens is not expressed” (Al Khatib et al, 2014: p. 809) and “in smaller specimens, the characters are subdued” (Smith, 2012: p. 215) are common in taxonomic descriptions and often refer cuticular specializations, such as carinae or grooves. Despite the importance of allometric reductions, developmental causes of these phenomena have never been revealed.…”
Section: Discussionmentioning
confidence: 99%